2006
DOI: 10.1089/hum.2006.17.589
|View full text |Cite
|
Sign up to set email alerts
|

Novelmfgl2Antisense Plasmid Inhibits Murinefgl2Expression and Ameliorates Murine Hepatitis Virus Type 3-Induced Fulminant Hepatitis in BALB/cJ Mice

Abstract: Our previous reports, both experimental and human studies, have shown the importance of fibrinogen-like protein-2 (fgl2) prothrombinase in the development of fulminant viral hepatitis, a disease with a mortality of more than 80% in cases lacking immediate organ transplantation. To interfere with this potentially effective target, a 322-bp mouse fgl2 (mfgl2) antisense plasmid complementary to the exon 1 sequence of the gene, including the translation initiation site AUG, was successfully constructed. A dose-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…The observations that neutralizing Abs to mfgl2 prevent both fibrin deposition and death from MHV-3 infection support its role as a coagulant [17] . Recent studies have shown that inhibition of reticuloendothelial cell mfgl2 expression through the use of gene-targeted fgl2-deficient (fgl2-/-) mice or targeted fgl2 gene with antisense mfgl2 results in the prevention of MHV-3-induced fibrin deposition, liver injury, and death [2,18] . Our study shows that fgl2 prothrombinase was expressed in malignant tumor tissues including colon, breast, lung, gastric, esophageal, and cervical tissues from patients and in HCC nude mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…The observations that neutralizing Abs to mfgl2 prevent both fibrin deposition and death from MHV-3 infection support its role as a coagulant [17] . Recent studies have shown that inhibition of reticuloendothelial cell mfgl2 expression through the use of gene-targeted fgl2-deficient (fgl2-/-) mice or targeted fgl2 gene with antisense mfgl2 results in the prevention of MHV-3-induced fibrin deposition, liver injury, and death [2,18] . Our study shows that fgl2 prothrombinase was expressed in malignant tumor tissues including colon, breast, lung, gastric, esophageal, and cervical tissues from patients and in HCC nude mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the importance of Fgl2/fibroleukin prothrombinase in both patients with HBV-ACLF and a fulminant hepatitis mouse model with murine hepatitis virus strain 3 (MHV-3) infection [12][13][14]. The mouse-fgl2 antisense administration remarkably increased the survival rate of mice with MHV-3-induced fulminant hepatitis [15,16]. A positive correlation was observed between human-fgl2 expression and the degree of liver injury, as indicated by the bilirubin levels.…”
Section: Pathophysiology Of Aclfmentioning
confidence: 99%
“…Therefore, gene therapy for treating ALF is still in its infancy. Several studies report successful development of gene therapy for ALF in animals, mostly mice [257][258][259][260][261][262][263][264][265][266][267]. The main non viral vectors used in theses references are siRNA antisense oligonucleotides and Zinc-finger nucleases (ZFNs).…”
Section: Acute Liver Failurementioning
confidence: 99%